Recycling tires for daily coverage of small and medium-sized landfills - Moreira, Amanda Rezende; Gonçalves, Helton Magno de Sousa; Figueiredo, Adriano Pereira de (Revista Verde de Agroecologia e Desenvolvimento Sustentável, 2021)
Recycling waste tires makes it possible to transform environmental liabilities into sustainable raw materials. This study proposes using waste tires as daily coverage of medium landfill cells in Itaporanga, Paraíba, to reduce the soil amount and the operational costs. We researched bibliographical materials addressing the topic. The field research was carried out during 90 days, verifying and analyzing the stages of production of cover mats from tires in the landfill. This recycling technique prevented the cell from running out quickly, increasing its useful life.